Previ, Petros e Funcef: Uma análise da alocaç\~ao das carteiras das três maiores entidades brasileiras de previdência complementar (2003-2013) - Bruno de Conti (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– At the end of 2014, the pension funds in Brazil held a portfolio of R 672 billion. About 45% of these resources are owned by the three largest entities of the country, namely, Previ, Petros and FUNCEF. This article aims to analyze in detail the evolution of the portfolios of these three entities over the period 2003-2013. We conclude that although they hold a higher proportion of investments in equities and structured investments - compared to the other pension funds - the portfolio management of these three entities is also very conservative, counting on a great concentration of resources allocated in government bonds. The article presents an analysis of the profile and management of these government bonds, and a sectoral division of the investments made by these entities. The analysis makes clear the importance of these three entities in: i) public companies privatization; ii) major national groups configuration; iii) infrastructure investments.
Keywords: H60; H54; 330; pension funds; Previ; Petros; Funcef; financing; portfolio choice